Prevalence and outcome of subclinical rheumatic heart disease in India: The RHEUMATIC (Rheumatic Heart Echo Utilisation and Monitoring Actuarial Trends in Indian Children) study. Issue 24 (10th November 2011) - Saxena, Anita; Ramakrishnan, Sivasubramanian; Roy, Ambuj; Seth, Sandeep; Krishnan, Anand; Misra, Puneet; Kalaivani, Mani; Bhargava, Balram; Flather, Marcus D; Poole-Wilson, Philip P A
Abstract : Objective: To study the prevalence and medium term outcome of subclinical rheumatic heart disease (RHD) in India. Design: Cross sectional echocardiographic screening study. Setting: School children aged 5–15 years living in rural areas of north India. Patients: A cross sectional echocardiographic screening study was carried out among 6270 randomly selected school children aged 5–15 years (10.8±2.6 years; 52.7% male). Of all the abnormal cases, 100 children (78%) were restudied at a mean follow-up of 15.4±6.6 months. Intervention: Echocardiographic screening. Main outcome measure: Echocardiography–Doppler criteria based prevalence of RHD. Results: Clinical examination detected mitral regurgitation in five patients and the estimated prevalence of clinical RHD was 0.8/1000 school children. Echocardiography–Doppler diagnosed RHD in 128 cases, giving a prevalence of 20.4/1000 school children (95% CI 16.9 to 23.9/1000 children). On multivariate analysis, older age (OR 1.93, 95% CI 1.29 to 2.88; p=0.001), female sex (OR 1.84, 95% CI 1.25 to 2.72; p=0.002) and government funded school student, which is a surrogate measure of lower socioeconomic status (OR 1.55, 95% CI 1.02 to 2.34; p=0.039) were found to be independent predictors of RHD. On follow up, the severity of subclinical RHD was non-progressive in 68 children (68%) while it worsened in four (4%) and regressed in 28 children (28%). Conclusions: The prevalence of RHD is several fold higher using echocardiographic screening compared with clinical examination. The prevalence is higher among girls and children of lower socioeconomic status. In the majority of cases, subclinical RHD appears to be non-progressive on medium term follow up. Routine echocardiographic screening may be indicated in populations at high risk of RHD.